2011
DOI: 10.1002/ajmg.b.31211
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of a promoter polymorphism in S100B, a putative risk variant for bipolar disorder

Abstract: Calcium-binding protein S100B has been implicated in the pathology of bipolar affective disorder (BPAD) and schizophrenia (SZ). S100B protein levels are elevated in serum of patients with both disorders compared to controls. We previously reported genetic association of a SNP in the promoter of S100B, rs3788266, with a psychotic form of BPAD. To test for genotypic effects of rs3788266 in vivo, S100B serum protein levels were measured in 350 Irish and German subjects of known S100B genotype. The functional effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 46 publications
0
20
1
Order By: Relevance
“…A number of previous studies have suggested that the levels of S100B protein are altered in patients with schizophrenia, with the general observation that S100B levels are increased [16,19,29,61-63]. While some controversy exists, studies suggest that medication status may alter S100B concentrations [25,31,41,43,44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of previous studies have suggested that the levels of S100B protein are altered in patients with schizophrenia, with the general observation that S100B levels are increased [16,19,29,61-63]. While some controversy exists, studies suggest that medication status may alter S100B concentrations [25,31,41,43,44].…”
Section: Resultsmentioning
confidence: 99%
“…At the protein level, findings suggest that S100B is increased in schizophrenia, and that these protein levels are correlated with medication, gender, age and illness severity [16,23-44]. Importantly, astrocytes express dopamine receptors (DA2Rs) and antipsychotic medications regulate the cellular release of S100B [45-48].…”
Section: Introductionmentioning
confidence: 99%
“…The search elicited 40 papers of which eight were reviews. 2,9,22,32,[34][35][36][37] From the 32 non-review papers, eight were focused on genetic studies, [38][39][40][41][42][43][44][45] one paper was focused on the role of S100B protein as a marker of suicidality, 46 another paper focused on S100B and cerebral palsy, 47 one paper was written in Japanese and was related to the levels of S100B in healthy subjects, 48 and another was on histological distribution on S100B immunopositive glia. 13 The latter 12 studies were excluded from the present review.…”
Section: Methodsmentioning
confidence: 99%
“…Although Yang et al [61, 62] did not find an association between S100B gene polymorphisms and MDD in a Chinese population, they revealed an influence on age of onset and subgroups (first-episode vs. recurrent episode depression) of MDD – A finding consistent with the dymanic glial concept of mood disorders. Remarkably, respective S100B polymorphisms are related to serum levels of this protein in healthy subjects and in patients with BD, and to messenger ribonucleic acid (mRNA) gene expression of S100B in the frontal cortex of healthy subjects [63, 64]. …”
Section: Serum S100b Is Elevated In Mood Disordersmentioning
confidence: 99%